The Multimodal Future of On-Street Parking. A Strategic Approach to Curbside Management. - Nadkarni, Rachel (My University, 2020)
This report is divided in two chapters. The first highlights the latest developments in curbside management and makes the case for municipalities to invest in curbside management programs including incorporating spaces for today’s newest mobility services. Many of these innovations are already being developed in Germany but need engaged municipalities to reach their full potential. The second chapter outlines a proposal for curbside policies that are broader and better equipped to incorporate any number of new vehicles or mobility services.
Keywords: Straßenrand; Parkraummanagement; Parkraumbewirtschaftung; Ruhender Verkehr; Straßenraum; Verkehrsfläche; Stadtverkehrsplanung; Kommunale Verkehrsplanung; Verkehrspolitik